Sterol divergence across eukaryotic kingdoms determines membrane susceptibility to saponins, a class of plant defense compounds - Malbor Dervishi; Jan Günther; Jinhui Li; Huriye Deniz Uzun; Hans Christian Bruun Hansen; Thomas Günther Pomorski; Anja Thoe Fuglsang; Viviana Monje; Søren Bak (Proceedings of the National Academy of Sciences, 2026)
Saponins are a class of plant-derived amphiphile defense compounds that disrupt cellular membranes, yet the basis for their selective toxicity remains unclear. Because membrane sterols diverged across the three major eukaryotic kingdoms from a shared biosynthetic precursor, we tested whether sterol identity governs membrane susceptibility to saponins. Using yeast, sterol supplementation, synthetic liposomes, and molecular dynamics simulations, we compared membranes containing zoosterols, mycosterols, or phytosterols. When a panel of structurally different saponins was tested, reduced ergosterol levels in yeast were consistently associated with decreased lytic activity. A similar reduction in susceptibility was observed when ergosterol was replaced by phytosterols in yeast. These trends were recapitulated in a simplified membrane system, where the sterol identity in large unilamellar vesicles strongly influenced saponin-induced lysis. The triterpenoid saponin α-hederin efficiently lysed membranes enriched in cholesterol or ergosterol, whereas membranes containing plant phytosterols were markedly resistant. In contrast, the steroidal saponin digitonin exhibited lower lytic activity and limited sterol selectivity. Molecular dynamic simulations revealed sterol-dependent clustering and membrane responses that paralleled experimental susceptibility. Together, these findings support a two-parameter model where structural characteristics of saponins together with sterol identity in the membrane are a primary determinant of saponin-induced membrane disruption. The differential compatibility between saponins and sterol classes provides a mechanistic framework for understanding cross-kingdom selectivity and sheds light on how plants avoid self-toxicity while deploying saponins for defense.